Toward Undogmatic Reading Narratology, Digital Humanities and Beyond - Flüh, Marie; Horstmann, Jan; Jacke, Janina; Schumacher, Mareike (Hamburg University Press, 2021)
Both Narratology and Digital Humanities look back on a remarkable history of research and progress. One after the other, the narratological and the digital research communities evolved into large international and interdisciplinary networks. While cooperation between the two disciplines would be possible and beneficial in many areas, they often still work in parallel rather than together. A workshop at Hamburg University brought together Literary Studies researchers from Narratology and from Digital Humanities to (a) discuss requirements for and possibilities of a digital operationalisation of analytical categories from Narratology and Literary Studies and (b) theoretically reflect upon possible connections between more traditional and digital approaches. The present volume combines the workshop contributions from both disciplines and thus attempts to further the bridge-building and dialogue.